Soil Science and Archaeology : Three Test Cases from Minoan Crete - Morris, Michael W. (Prehistory Monographs, 2002)
In this book Michael Morris presents a detailed study of the prehistoric landscape in three regions of Crete. He examines the development, stability, and physio-chemical composition of selected soils near three archaeological sites: Karphi, a Late Minoan IIIC ""Refuge Site""; Chrysokamino, a Final Neolithic to Late Minoan IIIB Farmhouse; Vronda and Kastro near Kavousi, two Late Minoan IIIC to Geometric Sites. Morris offers conclusions on the history of the Cretan landscape and its formation processes, and how those processes contribute to our understanding of the human use of the landscape. Th